Treatment of diabetes in elderly of 65 years. Review and utility of glp-1 in this group of patients (European Journal of Health Research, 2016)
The prevalence of overweight and obesity has increased very significantly in recent decades and is a major public health problem in Spain and in most developed countries. Overweight and obesity increase the risk of many other diseases such as cardiovascular disease, insulin resistance, type 2 diabetes, hypertension, dyslipidemia and certain types of cancers. In this context, the increase in life expectancy in our environment, determines that in nursing homes prevalence of diabetes has increased from 16 to 23 percent in the period 1996-2004. In addition there are to take into account that older adults with diabetes suffer from excess morbidity and mortality compared with those without diabetes, which together with its basic characteristics, complicating their management. It is often found in these patients polypharmacy, functional disabilities, as well as geriatric syndromes common as cognitive impairment and risk of falls. Recently it has been marketed lixisenatide (LIX). It is a GLP-1 short-acting. We conducted a study in which we aim to evaluate the effect on glycemic control and other metabolic variables by adding lixisenatide (LIX) a cohort of patients older than 65 years treated with combination therapy of oral agents and basal insulin (BOT).
Keywords: Diabetes; elderly; GLP-1 analogues